The Effort of Islamic Boarding School Leaders' to Improve the Potential of Students in Reading Arabic Books (A Study in Dayah Raudhatun Hasanah Namploh Manyang, Samalanga Sub-District, Bireuen District) - Mursyidi; Helmi; Musbani; Hayatun Nufus; Faisal (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
Islamic religious education is education that the role is very supportive in shaping each person's personality, and education that can instill good moral values ​​in everyday life. In studying the education, Islam also has order for the smooth teaching and learning process, in the process of learning the book also requires methods/ways to achieve the desired learning goals, the determination of teaching methods in a learning process is one step that must be taken by leader of the Islamic Boarding School. This research aims to determine the efforts of Islamic boarding schools leaders’ to improve the potential of students in reading Arabic books (a study in Dayah Raudhatun Hasanah Namploh Manyang, Samalanga Sub-District, Bireuen District). This study is a qualitative study. The technique of collecting the data is done by interview, observation and documentation study. The sources of data in this study were the leader of Dayah, teachers who were assigned to teach, teachers who assigned in the managerial field, daily implementers, and business people in Dayah area, student, and Dayah stakeholders. Research results show that; (1) carrying out the book learning process so that the potential of students in reading Arabic books increases, in this case the teacher's council uses several methods, namely lecture method, assignment, reading and training. (2) Supporting factors of implementing lecture method, assignment, reading and training are the teacher in giving more space direction to control students when the learning process occurs, the existence of this support from the teacher and students are very active in mastering the knowledge provided by their teacher. The inhibiting factor is the lack of cohesiveness between teachers and students in the field of teaching and learning and less creative in issuing constructive ideas.